Perubahan Pemaknaan Peran Perempuan Muslim dalam Pengasuhan Anak di Pedesaan Kawasan Prambanan - Muryanti, Muryanti (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
Muslim women worked in public sector in all variant jobs not only in urban area, but also in rural area phenomena. They had been doing it because of freedom, education, solidarity, or economic reason. When Muslim women worked in public sector, the new problems were appears, about care of children in the house as domestic work. These phenomenons were related to Indonesianâs culture and Islam perspective that believed the jobs of care of children was women burden. This article described about changing of meaning the role of Muslim women in the caring children. There were many institutions replaced care children, like day care etc. This article used qualitative research with observation and interview. The result of research, there were changing care of children in rural society. Before 2000, Muslim women were depend on family (extend family), neighbors, domestic worker, but in 2013, they prefered care of their children in the new institution (day care) because this institution gave early education to the child and save. But, majority Muslim women in this research believed that domestic works are their jobs.